HUBUNGAN KONSUMSI MAKANAN SUMBER ANTIOKSIDAN DAN KONSUMSI MAKANAN KALENG DENGAN KEJADIAN PREEKLAMPSIA DI RSUD DR. R. GOETHENG TAROENADIBRATA PURBALINGGA TAHUN 2015 - Wulandari, Nunik; Astuti, Dewi; ., Sumarni (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: RELATIONSHIP BETWEN CONSUMPTION OF FOOD SOURCES ANTIOXIDANTS AND FOOD CONSUMPTION IN CANS WITH PREECLAMPSIA IN Dr. R. GOETENG TAROENADIBRATAâ€™S HOSPITAL PURBALINGGA 2015. Preeclampsia is the onset of high blood pressure in pregnancy accompanied Proteinuria and edema at â‰¥ 20 weeks gestation. One of the causes of free radicals, free radicals can be treated by administration of antioxidants such as vitamins A, C, E, and beta carotene, superoxide dismutase, an antioxidant lipid and glutathione peroxidase and selenium, Besides canned food also causes an increase in blood pressure because they contain high sodium. Increased sodium intake causes the heart to pump harder to push blood volume increases through the space more narrow that the result is hypertension.To determine the relationship of the consumption of food sources of antioxidants and canned food with the incidence of preeclampsia in dr. R. Goeteng Taroenadibrataâ€™s Hospital Purbalingga 2015. Type of this research was analytic survey with case control approach. The research sample of 76 pregnant women. The sampling technique is done by using purposive sampling. Univariate analysis using frequency distribution and bivariate analysis using chi square test. Pregnant women rarely preeclampsia mostly consume food sources of antioxidants 24 people (63.2%) and preeclampsia pregnant women not to consume the majority of frequent food sources of antioxidants 26 people (68.4%). Pregnant women often consume mostly canned foods. There is a relationship between the consumption of food sources of antioxidants with the incidence of preeclampsia (Ï value 0.012), and there was no association between the consumption of canned food with the incidence of pre eclampsia (Ï value 0.088). There is a relationship between the consumption of food sources of antioxidants with the incidence of preeclampsia, and there was no association between the consumption of canned food with the incidence of pre eclampsia in Hospital Dr. R. Goeteng Taroenadibrata Purbalingga 2015.Â Keywords: Antioxidant, food in cans, Preeclampsia